2019
DOI: 10.1038/s41598-019-56914-w
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses through Toll-like receptor 3 require human-antigen-R-mediated Atp6v0d2 mRNA stabilization

Abstract: Toll-like receptor 3 (TLR3) recognizes double-stranded RNA derived from virus and its synthetic analogue, polyinosinic–polycytidylic acid [poly(I:C)]. Upon poly(I:C) binding, TLR3 activates transcription factors to express inflammatory cytokines and type I interferon. TLR3 is located in the endosomes and its recognition of poly(I:C) and activation of downstream signaling is regulated by endosomal acidification. However, the mechanism of post-transcriptional regulation in TLR3-mediated innate responses remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…First, the upregulated expression of Atp6v0d2 in BMDMs infected with L. donovani was not accompanied by the upregulation of the other V-ATPase components (Figure 4). This unorchestrated change of Atp6v0d2 expression among V-ATPase components was also reported in macrophages treated with a TLR3 agonist or osteopontin (Zainol et al, 2019;Dai et al, 2022). Second, the location of upregulated ATP6V0D2 did not overlap with a lysosomal marker LAMP1 (Figure 4), as opposed to a previous finding in BMDMs (Xia et al, 2019).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…First, the upregulated expression of Atp6v0d2 in BMDMs infected with L. donovani was not accompanied by the upregulation of the other V-ATPase components (Figure 4). This unorchestrated change of Atp6v0d2 expression among V-ATPase components was also reported in macrophages treated with a TLR3 agonist or osteopontin (Zainol et al, 2019;Dai et al, 2022). Second, the location of upregulated ATP6V0D2 did not overlap with a lysosomal marker LAMP1 (Figure 4), as opposed to a previous finding in BMDMs (Xia et al, 2019).…”
Section: Discussionsupporting
confidence: 67%
“…Although Atp6v0d2 upregulation is reported on macrophages infected with L. amazonesis (Kikuchi et al, 2001), the magnitude of upregulation was less than two-fold and much weaker than that found in L. donovani infection in vitro and in vivo, indicating the involvement of species-specific molecules of the parasites for induction of ATP6V0D2 in macrophages. It is reported that Atp6v0d2 expression is controlled by TFEB (Palmieri et al, 2011;Liu et al, 2019), NFATc1 (Kim et al, 2008;Oh et al, 2015;Kim et al, 2022), and ELAVL1 (Zainol et al, 2019). In the spleen of L. donovani-infected mice, we did not find transcriptional changes in any of Tfeb, Nfatc1, or Elavl1 (data not shown).…”
Section: Discussionmentioning
confidence: 51%
“…The pH of intracellular vesicles might also be important for proteolytic processing and ligand recognition of endosomal TLRs. Blockade of the acidification of intracellular vesicles resulted in impaired innate immune responses mediated by TLR3, TLR7, and TLR9 ( 22 , 23 ). The localization of nucleic acid-sensing TLRs in cellular compartments is also important for the initiation of cell-type-specific signaling pathways.…”
Section: Nucleic Acid-sensing Tlrsmentioning
confidence: 99%
“…Depending on the cell type, TLR3 can be located both on the surface of the cell and inside endosomes, as is the case for fibroblasts, or only within endosomes, as is the case for cDCs [ 96 ]. Once TLR3 binds to dsRNA, the adaptor molecule TIR-domain-containing adapter-inducing interferon-β (TRIF) becomes activated and initiates the phosphorylation and nuclear translocation of the transcription factors nuclear factor κB (NF-κB) and interferon regulatory factor 3 (IRF3) ( Figure 2 B) [ 97 , 98 , 99 ]. While NF-κB induces proinflammatory cytokines, IRF3 promotes the expression of IFN-I, such as IFN-β [ 97 ].…”
Section: Innate Immune Response and Components Recognizing Hmpvmentioning
confidence: 99%
“…Once TLR3 binds to dsRNA, the adaptor molecule TIR-domain-containing adapter-inducing interferon-β (TRIF) becomes activated and initiates the phosphorylation and nuclear translocation of the transcription factors nuclear factor κB (NF-κB) and interferon regulatory factor 3 (IRF3) ( Figure 2 B) [ 97 , 98 , 99 ]. While NF-κB induces proinflammatory cytokines, IRF3 promotes the expression of IFN-I, such as IFN-β [ 97 ]. Notably, the interaction between TLR3 and hMPV has not been studied thoroughly yet.…”
Section: Innate Immune Response and Components Recognizing Hmpvmentioning
confidence: 99%